Examining Oral Communication Apprehension, Competence and Performance among Tourism students in Vocational High School - Ryzky, Anggia Sri; Kusriandi, Wendi (Universitas Swadaya Gunung Jati, 2016)
This study, analyzed the students’ communication performance and competence in the speaking class. This study also measured the students’ communication apprehension level and its correlation with communication performance and competence. 30 students of second year students of SMK Pariwisata Kosgoro Cirebon took part in this study. The data were gathered through questionnaire, presentation test to get the score of communication performance and interview test to get the score of communication competence. The correlation study was used to investigate the relation of each variable. The result from the students’ performance showed that 66,7% of the students scored below the school standard score (75) and 70% of the students scored below standard score in the interview test. The participants showed the highest apprehension to public speaking and the lowest apprehension to group discussion. Their level of apprehension showed that 43.3% students were in moderate level and 56,7% students were in high level of apprehension. It was also found that communication apprehension was negatively correlated with communication performance. While the result from the correlation between communication apprehension and competence showed that there was a very low positive correlation but, there was a high positive correlation between communication competence and performance.